Comparison of surface roughness of nanofill and nanohybrid composite resin polished by aluminum oxide and diamond particle paste - Y., Yolanda; Aripin, Dudi; Hidayat, Opik Taofik (Padjadjaran Journal of Dentistry, 2017)
Introduction: The adequate finishing and polishing procedures might occur the restoration longivity, the color retention, and the good integrating with the surrounding environment. Methods: This study was conducted to determine the surface roughness of the nanofill composite with the nanohybrid composite polished by the aluminum oxide pastes and diamond polishing paste. This study was a pure experimental-in vitro study. The results of polishing on the resin composite surfaces was observed using the optical microscope at 500x magnification and given the score. The Krusskal-Wallis test was conducted to depict the data analysis. Result: The results showed that the resin composite group of the nanohybrid polished by both aluminum oxide and diamond particle had smoother surface than the resin composite of the nanofill. Conclusion: The conclusions of this study depicted that there were differences of polishing results using the aluminium oxide and diamond particle paste between the nanofill and nanohybrid resin composite surface roughness.